2018
DOI: 10.1186/s13023-018-0970-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of diabetes following pancreatic surgery in patients with congenital hyperinsulinism

Abstract: BackgroundCongenital hyperinsulinism (CHI) is the most common cause of persistent hypoglycaemia in infancy that leads to unfavourable neurological outcome if not treated adequately. In patients with severe diffuse CHI it remains under discussion whether pancreatic surgery should be performed or intensive medical treatment with the acceptance of recurrent episodes of mild hypoglycaemia is justified. Near-total pancreatectomy is associated with high rates of insulin-dependent diabetes mellitus and exocrine pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…The early results of the insights generated by the only patient-reported data source are consistent with the literature and other studies completed, including the genetics ( 1 , 2 ), the reported side-effects of current medications ( 3 , 20 , 21 ), the timing and development of post-pancreatectomy diabetes ( 22 , 23 ), and the neurological implications associated with prolonged hypoglycemia ( 2 4 ).…”
Section: Discussionsupporting
confidence: 72%
“…The early results of the insights generated by the only patient-reported data source are consistent with the literature and other studies completed, including the genetics ( 1 , 2 ), the reported side-effects of current medications ( 3 , 20 , 21 ), the timing and development of post-pancreatectomy diabetes ( 22 , 23 ), and the neurological implications associated with prolonged hypoglycemia ( 2 4 ).…”
Section: Discussionsupporting
confidence: 72%
“…Other pathogenic subgroups, which play a minor role in pediatric patients, are hereditary or chronic pancreatitis, pancreatectomy for trauma or congenital hyperinsulinism, iron overload because of thalassemia and hemochromatosis . Specific subgroups of pancreatic diabetes, such as congenital hyperinsulinism and hereditary chronic pancreatitis, were investigated in a small number of studies, which have been limited by small sample sizes …”
Section: Introductionmentioning
confidence: 99%
“…The age at onset of hypoglycemia reflects the severity of CHI. Welters et al [8] reported that in surgically treated CHI patient's insulin treatment needs to be intensified to achieve good glycaemic control. Our data furthermore emphasize the need for improved medical treatment options for patients with diazoxide and/or octreotide unresponsive CHI.…”
Section: Discussionmentioning
confidence: 99%